2020
DOI: 10.1038/s41598-020-76940-3
|View full text |Cite
|
Sign up to set email alerts
|

External error attribution dampens efferent-based predictions but not proprioceptive changes in hand localization

Abstract: In learning and adapting movements in changing conditions, people attribute the errors they experience to a combined weighting of internal or external sources. As such, error attribution that places more weight on external sources should lead to decreased updates in our internal models for movement of the limb or estimating the position of the effector, i.e. there should be reduced implicit learning. However, measures of implicit learning are the same whether or not we induce explicit adaptation with instructi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 64 publications
(162 reference statements)
4
19
0
Order By: Relevance
“…We found a significant main effect of training (F (1, 28) = 58.85, p < .001, ŋ² = 0.220), a significant main effect of localization type (F (1, 28) = 5.78, p = .023, ŋ² = 0.005) and a significant interaction between training and localization type (F (1, 28) = 17.77, p < .001, ŋ² = 0.009). This suggests that estimates of unseen hand location shifted following reach training with a rotated cursor and that the size of these shifts were slightly larger for active localization compared to passive localization (illustrated in figures 5C & 5D), as found in previous studies from our lab [11][12][13]. Since the focus of the current study is concerned with exploring these patterns in EDS, we then investigated group differences in active and passive localization shifts (by subtracting aligned localizations from rotated localizations to create a measure of localization shift) and conducted a 2 X 2 mixed design ANOVA on localization shifts with localization type (active or passive) as a within-subjects factor and group (EDS or control) as a between-subjects factor.…”
Section: Figure 4 Measures Of Implicit Learning No-cursor Reaches For Controls Are Shown In Red and Those For Eds Participants Are Shown supporting
confidence: 82%
See 1 more Smart Citation
“…We found a significant main effect of training (F (1, 28) = 58.85, p < .001, ŋ² = 0.220), a significant main effect of localization type (F (1, 28) = 5.78, p = .023, ŋ² = 0.005) and a significant interaction between training and localization type (F (1, 28) = 17.77, p < .001, ŋ² = 0.009). This suggests that estimates of unseen hand location shifted following reach training with a rotated cursor and that the size of these shifts were slightly larger for active localization compared to passive localization (illustrated in figures 5C & 5D), as found in previous studies from our lab [11][12][13]. Since the focus of the current study is concerned with exploring these patterns in EDS, we then investigated group differences in active and passive localization shifts (by subtracting aligned localizations from rotated localizations to create a measure of localization shift) and conducted a 2 X 2 mixed design ANOVA on localization shifts with localization type (active or passive) as a within-subjects factor and group (EDS or control) as a between-subjects factor.…”
Section: Figure 4 Measures Of Implicit Learning No-cursor Reaches For Controls Are Shown In Red and Those For Eds Participants Are Shown supporting
confidence: 82%
“…The hand localization tasks (figure 1B) were used to measure acuity of unseen hand localization and have been established as a reliable measure of proprioceptive abilities [9][10][11][12][13][14]. In the active hand localization tasks, participants moved their own hand to a self-chosen position on the arc, and thus both afferent and efferent information was available.…”
Section: Hand Localizationmentioning
confidence: 99%
“…More compelling evidence comes from previous studies where a strong correlation between these measures was found 24 , 26 . We have shown that the size of both proprioceptive and predictive components of hand localization shifts can predict separate components of reach aftereffects 41 . However, all evidence that hand localization shifts contribute to reach aftereffects is correlational, so that the mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 84%
“…In the second approach for measuring implicit adaptation, which uses error-clamped feedback to get at the time course of implicit adaptation, participants are instructed about the nature of the paradigm, prompted to ignore the visual feedback, and faced with unnaturally smooth reach trajectories throughout the task 12 , 40 . Since this context necessarily increases external error attribution it should also suppress implicit learning 41 . This could explain why error-clamped feedback paradigms slow down implicit adaptation compared to how it naturally occurs here.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the shift tends to range between 5 and 10 and remains relatively stable, evidenced by probing sensed hand position following passive hand displacement at various timepoints in an adaptation study (12,(29)(30)(31)(32)(33)(34)(35)(36). Similar to multisensory integration, this shift presumably reflects the operation of a system seeking to establish a unified percept from discrepant sensory signals.…”
Section: Introductionmentioning
confidence: 92%